1991
DOI: 10.1210/endo-128-4-1833
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Down-Modulation of Luteinizing Hormone Receptors by Prolactin: A Flow Cytometry Study*

Abstract: Although the binding, internalization, and regulation of LH, PRL, and their respective receptors have been extensively studied, it is not known whether the receptors are coordinately regulated. Using double labeling experiments, we have previously shown that receptor-bound LH and PRL can be colocalized in identical endosomes of granulosa cells. We hypothesize that high levels of PRL may induce a heterologous down-modulation of LH receptors, consequently reducing ovarian responsiveness to further gonadotropin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Denef and Andries [26] reported the paracrine interaction between lacto trophs and gonadotrophs in pituitary cell aggregates. Lane and Chen [27] recently suggested that PRL, in addi tion to inducing the internalization of its own receptors, also caused a down-modulation of unoccupied LH recep tors, indicating a close link between PRL and LH cells. However, after incubation with medium containing high K+, only the release of PRL was inhibited by prior in cubation with DA, but the release of LH and FSH was unaltered which probably illustrates different mecha nisms operating before and after treatment with medium containing high K + .…”
Section: Discussionmentioning
confidence: 99%
“…Denef and Andries [26] reported the paracrine interaction between lacto trophs and gonadotrophs in pituitary cell aggregates. Lane and Chen [27] recently suggested that PRL, in addi tion to inducing the internalization of its own receptors, also caused a down-modulation of unoccupied LH recep tors, indicating a close link between PRL and LH cells. However, after incubation with medium containing high K+, only the release of PRL was inhibited by prior in cubation with DA, but the release of LH and FSH was unaltered which probably illustrates different mecha nisms operating before and after treatment with medium containing high K + .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown experimentally that induced hyperprolactinemic rats demonstrated impaired ovarian function that was associated with a significant reduction in available LH-R [18,19]. Two different alternatively spliced forms of tLH-R (tLH-R insert and tLH-R trunc ) could be particularly important as receptor variants lacking the TM and IC region, since the secreted proteins would be capable of binding LH [34].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a marked increase in the circulating levels of PRL has been associated with incubation behavior, cessation of egg laying, and ovarian regression in the domestic turkey [15]. Exogenous administration of mammalian PRL has been shown to induce incubation behavior and/or gonadal regression and to cause a decline in circulating estrogen due to suppression in steroidogenic enzyme gene expression [15][16][17][18][19]. Ovarian regression may be achieved by a direct effect of PRL or may be attributable to reduced numbers of ovarian LH-Rs or both [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of this elevation in PRL secretion by bromocriptine administration has been shown to delay significantly the onset of anestrus in red deer hinds [3], suggesting that the breeding season is terminated partly by the effect of seasonal hyperprolactinemia. PRL may exert this effect directly at the level of the ovary through modulation of LH receptor (LH-R) expression [4]. Alternatively, elevated secretion of PRL may affect the GnRH axis through interaction with PRL receptors (PRL-R) in the brain [5].…”
Section: Introductionmentioning
confidence: 99%